Editorial - Oniwide, Oyetola (NIU Journal of Social Sciences, 2019)
This issue of KIU Journal of Social Sciences focuses on Development Studies, Entrepreneurship Studies, Legal Studies and Educational Management. Development Studies is a multi- and inter- disciplinary field of study (i.e. not a discipline) that seeks to understand social, economic, political, technological and cultural aspects of societal change. No wonder, Developmental psychologists study human growth and development over the lifespan, including physical, cognitive, social, intellectual, perceptual, personality and emotional growth. Developmental psychologists working in colleges and universities tend to focus primarily on research or teaching. That is why the first part of the Journal addresses issues in Development Studies such as civil society engament in attainment of sustainable goals, democracy, functional education, vocational training and so on. One of the papers argues that Civil Society Organization has potential roles to play in the effective implementation of the Sustainabl Development Goals as well as to enhance their engagement, impact and effectiveness in global development processes. Section two explores the role of entrepreneurship Studies in National Development. Entrepreneurship is focused on developing knowledge, skills, and understanding of how an innovative and creative idea, product, or process can be used to form a new and successful business or to help an existing firm to grow and expand. For this purpose Government also welcomes entrepreneurs to start their business. Entrepreneurs can change the way we live and work. If successful, their revolutions may improve our standard of living. In short, in addition to creating wealth from their entrepreneurial ventures, they also create jobs and the conditions for a flourishing society. With the help of various empiral examples, papers in this section are able to prove that GDP growth rate is positively related to index of industrial production while the poverty rate and government expenditure on national security have negative signs which is an indication of the high rate of unemployment in Nigeria as many able bodied youth and graduates are not employed and as such, depended on the working population for survival which increases the rate of abject poverty. One of the papers, therefore, suggests that government should not only integrate entrepreneurship education as an integral part of the curriculum across all levels of education but should also establish skills acquisition centres across the country to reduce youth unemployment stem down the rate of poverty and insecurity in the country.. In today’s world, Excellence in legal education and research is extremely important, because it will help shape the quality of the rule of law . The invaluable experiences that legal education can offer to future lawyers are several. Primary among them is exposure. ... These are essential for the intelligent practice of law. This is why the third section of this edition is devoted to issues in Legal Studies such as legal duties of personnels in Secondary Schools, Protection of Teachers’ Rights and Professional Footballers’ Rights. One of the papers recommends the continuous improvement of awareness of legal duties through seminars; workshops; training of school principals on Education Law as well as updating Students Handbook to upgrade rules and penalties for violation. The last section which centres on Education Management features papers meant to helps in decision making and problem –solving, communication and managing information and building effective teams. It is recommended that participation in training and developmental programmes should be encouraged, to keep them abreast of current knowledge of research and teaching and to reduce redundancy. In all, this issue of KIU Journal of Social Sciences contains certain theoretical and empirical papers that keeing to provide solutions to one societal problem or the other. There is therefore something for everyone in this edition.